A novel compact wideband directional monopole antenna for use in radar applications - Jangi Golezani, Javad; Abbak, Mehmet; Akduman, Ibrahim (IEEE, 2012)
A novel compact directional monopole antenna in microstrip technology is presented. Basic aim of this paper is to maintain a tradeoff between the size and directivity of the antenna for use in radar and microwave imaging systems. Dimensions of the antenna are considerably miniaturized in comparison with conventional directional antennas. The main effort is to convert an Omni-directional radiation pattern of a compact monopole antenna to the desired directional radiation pattern, by using a novel ground plane, and a parasitic element. The ground plane and parasitic element are accurately designed in a way that make the surface currents of radiating elements to move toward the desired direction, which increase the radiation density in the preferred direction and also decrease the radiation intensity in the opposite sides. Simulations confirm a good directional characteristic of the antenna at the frequencies between 5 and 9 GHz. Gain of the antenna is increased over 5 dBi at the desired frequencies. Also Half Power Beam Width (HPBW) of the antenna is significantly decreased. Return-loss bandwidth of the antenna covers the frequencies among 5–9 GHz. Measurements confirm the simulations and desired directional characteristic and return-los bandwidth of the antenna. Miniaturized size and a good directional characteristic of the antenna make it possible to use it in the microwave imaging systems and radar applications.